Constructing Paris in the Age of Revolution - Potofsky, A. author. aut Link
XVII, 345 p. 46 illus.
Keywords: Examining the social and political history of workers and entrepreneurs engaged in constructing the French capital from 1763-1815, this book argues that Paris construction was a core sector in which 'archaic' and 'innovative' practices were symbiotically used by guilds, the state, and enterprises to launch the commercial revolution in France.